Miniature vessels from the Neolithic site at Čatež-Sredno polje - Tomaž, Alenka (Documenta Praehistorica, 2005)
Archaeologists use models based on ethnographic analogy and theory to recreate the meanings of symbols, but rarely can the archaeological data by itself provide us with a story. The extensive excavation at Neolithic Čate-Sredno polje provided us with new information concerning Neolithic society in the first half of the 5th millennium B.C. in Slovenia. The abundance of pottery finds offered a huge opportunity to explore several aspects of pottery production. In this article a closer look at one group of pottery finds will be presented. A detailed picture of the symbolic aspects of miniature vessels will be presented in terms of their production, use, function, and distribution.
Keywords: arheološke najdbe; neolitik; ceramic; keramika